CHOROIDAL NEOVASCULAR MEMBRANE AFTER FINE-NEEDLE ASPIRATION BIOPSY OF VITREORETINAL LYMPHOMA. Issue Volume 16:Issues 1(2022) (27th December 2019) - Mashayekhi, Arman; Mazloumi, Mehdi; Shields, Carol L.; Shields, Jerry A.
Abstract : We report the rare development of choroidal neovascular membrane at the site of diagnostic transvitreal fine-needle aspiration biopsy of subretinal pigment epithelial infiltrates in an eye with vitreoretinal lymphoma. Abstract : Purpose: To report development of choroidal neovascular membrane at the site of diagnostic transvitreal fine-needle aspiration biopsy of subretinal pigment epithelial infiltrates in an eye with vitreoretinal lymphoma. Methods: Case report. A 75-year-old white woman with 14-month history of bilateral vitritis. Results: Examination showed vitreous infiltration in both eyes and yellow-white subretinal pigment epithelial infiltrates temporally in the left eye. Visual acuity was 20/400 in both eyes. Transvitreal fine-needle aspiration biopsy of subretinal pigment epithelial infiltrate in the left eye using a long 27-gauge needle attached to a 10-mL syringe revealed large B-cell lymphoma. Treatment was initiated with monthly intravitreal injections of melphalan (10 μ g/0.05 mL) to both eyes. One month after first injection, visual acuity in the left eye had decreased to hand motion, and new ill-defined patches of retinal whitening were noticeable in the temporal macular area. Intravenous fluorescein angiography and optical coherence tomography angiography showed large choroidal neovascular membrane temporally at the site of previous fine-needle aspiration biopsy. Four monthly injections of intravitreal bevacizumab (1.25 mg/0.05 mL) resulted in complete regression of choroidal neovascular membrane with improvement of visual acuity to 20/100 in the left eye. Conclusion: This case demonstrates the rare development of choroidal neovascular membrane at the site of diagnostic transvitreal fine-needle aspiration biopsy of subretinal pigment epithelial infiltrates in an eye with vitreoretinal lymphoma.